Egyptian delta archaeology : short studies in honour of Willem van Haarlem - Haarlem, W. M. van; Bercken, Ben van den (Sidestone Press, 2021)
If you want to understand ancient Egypt, the Nile Delta is of key importance. Excavations and surveys in the Delta keep unearthing new information about how the ancient Egyptians lived, how they envisaged the afterlife and how they interacted with other cultures. The study of finds from the Delta gives us a glimpse into the beliefs and everyday life of the ancient Egyptians.00From 1979 to 2014 Willem van Haarlem worked on several archaeological sites in the Nile Delta, focusing on the excavations at Tell Ibrahim Awad in the eastern Delta from 1991 onward. At the same time he was curator of Egyptian Antiquities at the Allard Pierson, the heritage collections of the University of Amsterdam. On the occasion of his retirement a number of archaeologists, Egyptologists and museum curators have written a series of short studies in his honour, varying from current excavation results from Delta sites to new or renewed research into museum objects from this region. This book offers a rich palette of subjects to scholars interested in Delta archaeology and above all provides hitherto unpublished materials from excavations and museum depots that will inspire the next generation of Nile Delta scholars.0.